The evolution of ventral intermediate nucleus targeting in MRI-guided focused ultrasound thalamotomy for essential tremor: an international multi-center evaluation - Jameel, Ayesha; Akgun, Sena; Yousif, Nada; Smith, Joely; Jones, Brynmor; Nandi, Dipankar; Bain, Peter; Gedroyc, Wladyslaw (Frontiers in Neurology, 2024)
Background: The Ventral intermediate nucleus (VIM) is the premiere target in Magnetic Resonance Guided Focused Ultrasound (MRgFUS) thalamotomy for tremor; however, there is no consensus on the optimal coordinates for ablation. This study aims to ascertain the various international VIM targeting approaches (VIM-TA) and any evolution in practice. Methods: International MRgFUS centres were invited to share VIM-TAs in 2019 and 2021. Analysis of anatomical landmarks and/or tractography used, and any change in practice was conducted. Each VIM-TA was mapped in relation to the mid-commissural point onto a 3D thalamic nucleus model created from Schaltenbrand-Wahren Atlas. Results: Of 39 centres invited, 30 participated across the study period; providing VIM-TAs from 26 centres in 2019 and 23 in 2021. Results are reported as percentages of the number of participating centres in that year. In 2019, 96.2% centres (n=25) and in 2021, 95.7% centres (n=22) based targeting on anatomical landmarks rather than tractography. Increased adoption of tractography in clinical practice and/or for research was noted, 34.6% to 78.3%. There was a statistically significant change in VIM-TAs in the superior-inferior plane across the study period; VIM-TAs 2mm above the intercommisural-line (ICL) increased from 16.0% in 2019 to 40.9% in 2021 (WRST, p<0.05). This position is mapped at the centre of VIM on the 3D thalamic model created based on the Schaltenbrand-Wahren Atlas. In contrast, the VIM-TA medial-lateral and anterior-posterior positions remained stable. In 2022, 63.3% of participating centres provided the rationale for their VIM-TAs and key demographics. Centres were more likely to target 2mm above ICL, with increased experience (more than 100 treatments) and/or if they were North American. Conclusions: Across the study period, FUS centres have evolved their VIM targeting superiorly to target the centre of the VIM (2mm above ICL) and increased the adoption of tractography to aid VIM localisation. This phenomenon is seen across autonomous international centres, suggesting it is a more optimal site for FUS thalamotomy in tremor.